The use of religious resources in helping victims of workplace mobbing - Vveinhardt, Jolita; Deikus, Mykolas (Frontiers in Psychology, 2023)
Research shows that in providing assistance to individuals who have experienced psychological traumas, it is beneficial not only to take into account the specific religious spiritual needs but also to employ religious resources. Although the role of religious counsellors using various psychological theories in helping to cope with traumatising experiences is acknowledged, there is still a lack of a conceptualising approach to the possibilities of employing religious resources used in Christian spiritual assistance, seeking to help cope with the effects of workplace mobbing. Therefore, this study aims to conceptualise the perspective of integrating Christian spiritual assistance resources in overcoming the individual consequences of workplace mobbing. This review is based on an interdisciplinary approach and abundant literature of psychology, psychotherapy and theology sciences. The article details the main physical, psychological and social aspects of damage to the person, caused by mobbing, which provide for a corresponding triple assistance perspective. After highlighting the essential resources provided by the Christian religion for coping with traumatic experiences, the necessity to consider the religious needs of the victims of mobbing is reasoned and the possibilities of using religious spiritual resources are discussed. In the context of helping victims of mobbing, two main functions of Christian spiritual assistance are distinguished and discussed: auxiliary and main. The results of this review are a useful resource for lay and religious counsellors and encourage their collaboration. The research findings also provide a basis for further research on the use of religious resources in the context of helping victims of mobbing.